Jigsaw and Numbered-Heads Together in Teaching Reading Comprehension for Low and High Critical Thinking Students - Jarwanto Jarwanto; Suwandi Suwandi; Zulfa Sakhiyya (Universitas Negeri Semarang, 2022)
This research aims to find out whether Jigsaw technique and N-H-T technique are effective in teaching reading comprehension to high and low critical thinking students. This research used experimental study that was conducted at SMAIT Bina Amal Semarang. The population of this research was the Tenth Graders of SMAIT Bina Amal Semarang. Two classes were selected as sample through a cluster random sampling. Each class was classified into two groups (the students having high and low critical thinking). The techniques to collect the data was multiple choice test to obtain the data of students with high and low critical thinking based on their reading comprehension result. The two instruments were tried out to obtain the valid and reliable items. The data was analysed by using multifactor analysis of ANOVA 2x2. Before conducting the ANOVA test, normality and homogeneity tests were conducted. Based on the findings, it can be concluded that there is no significant difference statistically between both techniques to students with high and low critical thinking in teaching reading due to the learning process at this school used both online and offline learning (students attended school five times in two weeks based on attendance number) also the allocation time of teaching learning was decreased during Covid-19 pandemic.